Extracting implicit density functions from short term interest rate options - Hannah Nielsen (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
Using option prices the expectations of the market participants concerning the underlying asset can be extracted as well as the uncertainty surrounding these expectations. In this paper a mixture of lognormal density functions will be assumed to analyze options on three-month Euribor futures for the period between August and November 2000. During this period the ECB raised the interest rates and intervened in the exchange markets, both actions that could have an effect on the expectations of a short term interest rate. As will be shown the expected mean as well as the higher moments of the distribution show quite large movements, which can in part be associated directly with these interventions.
urn:nbn:de:kobv:11-10049957
Keywords: G13; E44; E52; C13; 330; monetary policy; implicit density function; interest rate options; market expectations